A community based cross sectional study to estimate total cardiovascular risk in rural Punjab - Vikramaditya, Bibhava; Satija, Mahesh; Chaudhary, Anurag; Sharma, Sarit; Girdhar, Sangeeta; Bansal, Priya (International Journal Of Community Medicine And Public Health, 2017)
Background: Cardiovascular diseases (CVD) are leading cause of non communicable deaths in India. CVD risk prediction charts by World Health Organization/International Society of Hypertension (WHO/ISH) are designed for implementing timely preventive measures. The objective of the study was to assess the prevalence of CVD risk parameters and to estimate total CVD risk among adults aged ≥40 years, using the WHO/ISH risk charts alone and also to assess the effect of the inclusion of additional criteria on CVD risk. Methods: A community based cross sectional study was conducted in fifteen villages of Ludhiana district under rural health training centre of Department of Community Medicine, Dayanand Medical College & Hospital, Ludhiana, Punjab. Desired information was obtained using WHO STEPS survey (STEP wise approach to surveillance) from 324 adults aged ≥40 years. Anthropometric, clinical and laboratory measurements were also performed. WHO/ISH risk prediction chart for South East Asian region (SEAR-D) was used to assess the cardiovascular risk among the subjects. Results: WHO/ISH risk prediction charts identified 16.0% of the subjects with high risk (≥20%) of developing a cardiovascular event. The study population showed higher prevalence of physical inactivity, obesity, abdominal obesity, hypertension and diabetes. Amongst high risk CVD group, maximum prevalence was of hypertension and high perceived stress level. However, the proportion of high CVD risk (≥20%) increased to 33.6% when subjects with blood pressure ≥160/100 mmHg and /or on hypertension medication were added as high risk. Conclusions: A substantial proportion of this community is at high risk of developing cardiovascular diseases.